Pengaruh Quality of Work Life Terhadap Job Performance Pada Karyawan Generasi Z di Perusahaan Startup di Jakarta - Alamanda, Winda; Riyanti, Benedicta P. Dwi (Jurnal Online Psikogenesis, 2023)
This study aims to determine the effect of quality-of-life work/quality of work life on job performance for Generation Z employees who work with start-up companies in Jakarta. This research hypothesizes that there is an effect on the quality of work life on job performance in Generation Z employees at start-up companies in Jakarta. The participants of this research are 100 Generation Z employees who work with startup companies in Jakarta. Sampling using a convenient sampling technique. This study uses a simple regression test technique. The results of data analysis show that there is a significant effect on quality of work life on job performance for generation Z employees at startup companies in Jakarta (F=16.795 with R2 =. 146; p=. 000). That is, QWL has a significant effect of 14.6% on job performance. The results of the descriptive analysis show that the distribution of scores for the QWL dimensions, namely the dimensions of health & and well-being, job security, job satisfaction, and competency development are in the highest category. Only the QWL (work and non-work life balance) dimensions are in the low and medium categories. Suggestions from the results of this study that QWL is important to be considered and managed properly by the company's management Suggestions from the results of this study that QWL is important to be considered and managed properly by the company's management, especially for the dimensions of work and non-work life balance. However, it needs to pay attention to other factors that affect employee job performance.